دراسة في وبائية إنتشار االوالي المعوية في االنسان في مدينة بغداد - نايف, حنان جواد; مجيد, لهيب جمال; عبد الوهاب, افتخار (Al-Nahrain Journal of Science, 2011)
800 stool samples were collected from Medical City hospital in Baghdad for the period from 1/January – 31/ December 2008. 596 cases of parasites were diagnosed (74.5%), which recorded: 53.18% in Entamoeba histolytica, 6.54% in Giardia lamblia & 40.26% in Blastocystis hominis. The survey also showed that the highest rate of infection ( 43.62%) was recorded in age group 21 – 40 years followed by age group under 20 years (22.48%) and the lowest 7.88% in age group (greater than 60 years old). There were a difference in proportion of infection between females and males, the ratio is rised in E.histolytica in females in two groups and reduced in other two groups, while the infection rate in males was higher than females in G.lamblia and B.hominis. While the ratio of infection by months of the year, it showed that the highest number of infection with E.histolytica in November (71.66%), and G.lamblia in September (17.94%), and B.hominis in February (63.15%). Co-infection was recorded between, E.histolytica and B.hominis, 71%, and B.hominis and G.lamblia 29% from 7 cases .